Loops and networks in control of Francisella tularensis virulence. (August 2009) - Meibom, Karin L; Barel, Monique; Charbit, Alain
Francisella tularensis is a highly infectious, Gram-negative bacterium responsible for the disease tularemia in a broad variety of animals, including humans. F. tularensis intracellular multiplication occurs mainly in macrophages. However, F. tularensis is able to infect many other cell types, including other phagocytic (dendritic cells, polymorphonuclear leukocytes) and nonphagocytic (alveolar epithelial cells, hepatocytes, endothelial cells and fibroblasts) cells. The ability of professional phagocytic cells to engulf and kill microbes is an essential component of innate defense. The ability of F. tularensis to impair phagocyte function and survive in the cytosol of infected cells thus constitutes a central aspect of its virulence. The F. tularensis intracellular lifecycle relies on the tightly regulated expression of a series of genes. The unraveling secrets of the regulatory cascades governing the regulation of virulence of F. tularensis will be discussed along with future challenges yet to be solved.